The Prognosis and Recovery of Aphasia Related to Stroke Lesion - Sul, Bomi (Ann Rehabil Med, 2016)
OBJECTIVE: To investigate the effects of specific brain lesions on prognosis and recovery of post-stroke aphasia, and to assess the characteristic pattern of recovery. METHODS: Total of 15 subjects with first-ever, left hemisphere stroke, who were right handed, and who completed language assessment using the Korean version of the Western Aphasia Battery (K-WAB) at least twice during the subacute and chronic stages of stroke, were included. The brain lesions of the participants were evaluated using MRI-cron, SPM8, and Talairach Daemon software. RESULTS: Subtraction of the lesion overlap map of the participants who showed more than 30% improvement in the aphasia quotient (AQ) by the time of their chronic stage (n=9) from the lesion overlap map of those who did not show more than 30% improvement in the AQ (n=6) revealed a strong relationship with Broca's area, inferior prefrontal gyrus, premotor cortex, and a less strong relationship with Wernicke's area and superior and middle temporal gyri. The culprit lesion related to poor prognosis, after grouping the subjects according to their AQ score in the chronic stage (a cut score of 50), revealed a strong relationship with Broca's area, superior temporal gyrus, and a less strong relationship with Wernicke's area, prefrontal cortex, and inferior frontal gyrus. CONCLUSION: Brain lesions in the Broca's area, inferior prefrontal gyrus, and premotor cortex may be related to slow recovery of aphasia in patients with left hemisphere stroke. Furthermore, involvement of Broca's area and superior temporal gyrus may be associated with poor prognosis of post-stroke aphasia.